Biogeografia do gênero Rauvolfia L. (Apocynaceae, Rauvolfioideae) - Vidal Junior, João de Deus (Universidade Federal de São Carlos, 2014)
Rauvolfia L. is a pantropical genus with 70 species distributed throughout America, Africa and Asia, also being present in several remote islands like Hawaii and French Polynesia. Although having an estimated age of 34 million years, the genus has a wide distribution as a result of its remarkable dispersal capacity, given its distribution associated with water bodies and the fact that its fruits are a food source for many bird species, placing Rauvolfia as a highly interesting group for biogeographical studies. Based on this, we produced distribution maps for the 70 species of the genus from occurrence data obtained from herbarium sheets and revision articles, which were digitalized and georeferenced. Species with similar distribution patterns were grouped and their maps were produced and compared with maps of topography and hydrography. We analyzed this distribution together with the most recent phylogenetic hypothesis for the group to infer the distribution of ancestral nodes and to identify barriers in the distribution among sister groups. The phylogeny used was based on chloroplast markers, while divergence timing was estimated by molecular clock, calculated for the whole tribe Vinceae Duby in a parallel study. Softwares S-DIVA and VIP were used for biogeographical reconstructions, which were interpreted within the context of current biogeographical hypotheses. The genus Rauvolfia is mainly limited by climatic and geographic factors. Moreover, while some vicariance episodes were identified, much of the patterns observed for Rauvolfia present distribution were attributed to long-distance dispersal events, reinforcing the role of dispersal in current discussions about angiosperm biogeography.
Biogeography of the genus Rauvolfia L. (Apocynaceae, Rauvolfioideae)
Keywords: Rauvolfia L. - biogeografia; Rauvolfia L. - biogeography; Sementes - dispersão; Seeds - Dispersal; Filogenia; Phylogeny; Análise de vicariância; Vicariance analyzis; CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL